Staying aspirations among Hungarian minority students in Central and Eastern Europe - Sütő, Zsuzsanna (Central European Journal of Educational Research, 2025)
Research on youth mobility in Central and Eastern Europe has primarily focused on migration intentions and the drivers of out-migration. Much less attention has been paid to the motivations behind staying, particularly among national minority youth living in peripheral regions. This study examines the staying aspirations of Hungarian minority university students in Central and Eastern Europe and explores the demographic, human, economic, and sociocultural factors that shape their intentions to remain in their home regions. Drawing on the aspiration–capability framework developed by Carling and Schewel, the study analyses survey data from 1,107 hungarian minority students enrolled in higher education institutions across several Central and Eastern European countries. Using multivariate statistical models, the analysis investigates how different forms of capital and regional embeddedness influence students’ aspirations to stay rather than migrate. The findings suggest that staying aspirations are not merely the result of limited mobility opportunities. Instead, they are strongly associated with sociocultural embeddedness, minority community ties, and forms of social capital that connect students to their local environments. These results challenge the dominant migration-centred perspective in mobility research and highlight the importance of immobility as an active and meaningful life strategy. The study contributes to the growing literature on youth immobility by demonstrating how minority status and regional attachment shape mobility aspirations in Central and Eastern Europe.